Detection of Staphylococcus Enterotoxin sea and seb in Milk Samples by Duplex Droplet Digital PCR - Xiaoyue Wei; Wenzhou Wang; Tong Wang; Yuhua Yang; Yahui Guo; Lijin Long; Jiaming Fan; Fanliang Meng; Wentao Liu; Wanting Wang; Yakun Zhao; Jianling Chen; et al. (Journal of Food Protection)
This study sought to develop a method to accurately and quantitatively measure the staphylococcal enterotoxin genes sea and seb in milk samples using duplex droplet digital polymerase chain reaction (ddPCR). Specific primers and probes were designed for sea and seb. By optimizing the concentrations of primers and probes and the annealing temperature, a duplex ddPCR detection system was established, and the specificity and sensitivity of the method were evaluated. Standard curves were generated using plasmid DNA, pure cultures, and milk samples spiked with Staphylococcus aureus, and a high correlation coefficient (R2 = 0.99) was achieved within the ranges of 1 × 101–1 × 105 copies/μL, 2 × 103–2 × 107 cfu/mL, and 2 × 103–2 × 107 cfu/mL, respectively, for these samples. Using the gradient dilution method with pure cultures and milk samples spiked with S. aureus, the limit of detection (LOD) was 2 × 103 cfu/mL using primers targeting both enterotoxin genes. The test results exhibited good accuracy and repeatability, with three parallel repetitions revealing intra-assay and inter-assay coefficient of variations of <10% and <20%, respectively. When milk samples were spiked with S. aureus at concentrations of 2 × 101 and 2 × 102 cfu/mL, both sea and seb could be detected during the fourth and fifth hours of pre-enrichment, respectively. This study successfully established a duplex ddPCR detection system with high sensitivity and specificity for the quantitative detection of sea and seb in milk samples, thereby permitting the accurate detection of S. aureus directly in milk specimens.